2017
DOI: 10.1039/c7nr04582d
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser induced robust periodic nanoripple structured mesh for highly efficient oil–water separation

Abstract: Marine oil spills have induced severe water pollution and threatened sea ecosystems, which also result in a loss of energy resources. To deal with this problem, much work has been done for using superhydrophobic or superhydrophilic mesh for oil-water separation. Nevertheless, there are still great challenges in the rapid fabrication of extremely durable mesh with superwetting properties, particularly considering the highly efficient oil-water separation. In this study, we present a simple, efficient method to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
146
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 315 publications
(147 citation statements)
references
References 43 publications
1
146
0
Order By: Relevance
“…Based on the principles mentioned above, novel materials were invented and fabricated as proof‐of‐concept. Oil–water separators are generally porous meshes, foams and sponges made from a wide range of materials, including metal, polymers, ceramics, fabrics, cellulose‐based derivatives, particles, and novel nanomaterials . Recently, Wang et al reported a highly compressible wood sponge with spring‐like lamellar structure (Figure b–d), which was fabricated by sequential chemical treatment, freeze drying and chemical vapor deposition of natural balsa wood.…”
Section: Applicationsmentioning
confidence: 99%
“…Based on the principles mentioned above, novel materials were invented and fabricated as proof‐of‐concept. Oil–water separators are generally porous meshes, foams and sponges made from a wide range of materials, including metal, polymers, ceramics, fabrics, cellulose‐based derivatives, particles, and novel nanomaterials . Recently, Wang et al reported a highly compressible wood sponge with spring‐like lamellar structure (Figure b–d), which was fabricated by sequential chemical treatment, freeze drying and chemical vapor deposition of natural balsa wood.…”
Section: Applicationsmentioning
confidence: 99%
“…In this regards, metal oxide, inorganic clay, magnetic materials, polymer microfiber bundles, polymer-based superhydrophobic materials, and sponge-like aerogels have been explored for oil-water separation because of its high surface area, coupled with excellent mechanochemical stability, and hydrophobicity [4,[9][10][11][12][13]. In addition, metal meshes have also been reported explored for oil-water separation but have limitations of low separation efficiency and poor cyclability [14,15]. However, the high cost of the chemicals required for the synthesis of above materials and associated environmental and ecological concerns restrict their widespread use [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…38 and 39 [104,105]. Duan et al [106] fabricated stainless-steel Fig. 32 a Rose pattern formed on surface of graphene after femtosecond laser fabricating; b roses in nature [89] Fig.…”
Section: Superoleophobic Surface and Oil-water Separationmentioning
confidence: 99%
“…Schematic of drilling microholes on titanium foil[104] SEM images of surface microstructure of titanium foil after femtosecond laser fabrication[105] Untreated stainless steel grid and stainless-steel grid after laser fabrication; b SEM images of pristine stainless-steel mesh; c-e SEM images after laser fabrication at different magnifications[106] Multiphoton polymerization fabrication steps: (I) photopolymerization at the laser focus; (II) processing samples by laser direct writing; (III) organic developer washes unexposed material; (IV) processed 3D scaffold[125] 1 3…”
mentioning
confidence: 99%